2021
DOI: 10.3389/fmicb.2021.675552
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Inoculants Mitigating Water Scarcity in Tomato: The Importance of Long-Term in vivo Experiments

Abstract: Global population growth and climate change raise a challenge to agriculture, which, combined with the issues concerning the use of chemical fertilizers, have generated increasing attention in the use of plant-associated bacteria as a sustainable strategy in agri-food systems. The objective of this study is to evaluate the ability of five bacterial strains, previously isolated from the rhizosphere or endosphere of plants adapted to harsh environmental conditions, to act as potential plant biofertilizers in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
(62 reference statements)
1
14
0
Order By: Relevance
“…Moreover, previous research on different crops concluded that PGPB inoculation must be combined with chemical treatment to have the best results on plant growth (Bona et al 2018;Cordero et al 2018;Angulo et al 2020). The same assertion was reported for the tomato species: several authors wrote about the positive effect of microbial inoculation under environmental or biological stresses such as drought, salinity (Mannino et al 2020;Riva et al 2021), nutrient de ciency in soils, and pathogens; anyway, the few studies that compared bio-and chemical fertilisation, described a lower yield in fruit production when chemicals have been completely replaced by PGPB inoculations (Adesemoye et al 2009; Ye et al 2020). The results of these mentioned works do not encourage the tomato growers to apply the biofertilisation.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Moreover, previous research on different crops concluded that PGPB inoculation must be combined with chemical treatment to have the best results on plant growth (Bona et al 2018;Cordero et al 2018;Angulo et al 2020). The same assertion was reported for the tomato species: several authors wrote about the positive effect of microbial inoculation under environmental or biological stresses such as drought, salinity (Mannino et al 2020;Riva et al 2021), nutrient de ciency in soils, and pathogens; anyway, the few studies that compared bio-and chemical fertilisation, described a lower yield in fruit production when chemicals have been completely replaced by PGPB inoculations (Adesemoye et al 2009; Ye et al 2020). The results of these mentioned works do not encourage the tomato growers to apply the biofertilisation.…”
Section: Introductionsupporting
confidence: 58%
“…After the positive results obtained by in vitro screening for the selected potential PGP bacteria, in agreement with the bottom-up approach suggested by Riva et al (2021), we performed eld experiments to test the real effect of these bacterial inoculants on plant production of three different tomato varieties.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Similar results were reported by Fernandes et al [39], who tested the same biostimulants on common bean and suggested water-stress-mitigating effects of the tested biostimulants on nutritional value parameters such as fat, proteins and ash content. These results could be associated with the improved nutrient status of plants, since previous studies have established the positive role of arbuscular mycorrhizal fungi (AMF), bacteria and seaweed extracts on nutrient uptake [31,35,[46][47][48]. Moreover, the application of biostimulants containing chelated metals improved specific nutritional aspects of tomato fruit under full irrigation, which could be considered as a sustainable tool to improve fruit quality.…”
Section: Resultsmentioning
confidence: 98%
“…In addition to their culinary role in the human diet, tomatoes represent a food source with low energetic value and with unique constituents that may positively affect health, since they are rich in vitamins, minerals, lycopene, β-carotene and anticancer agents [7,27]. The use of biostimulants in tomato crops is becoming popular, since positive results have been observed in terms of yield and fruit quality, especially under abiotic stress conditions, where plants showed increased resilience [28][29][30][31][32]. For example, the foliar application of a plant-based biostimulant containing flavonoids and organic acids on tomato plants grown under stress conditions showed protective effects on the functions of the photosynthetic machinery [33].…”
Section: Introductionmentioning
confidence: 99%